Pengaruh Program Waktu Perebusan pada Horizontal Sterilizer Pabrik Kapasitas 30 Ton TBS/Jam terhadap Unstripped Bunch (USB), Fruit Loss in Empty Bunch (FEB) dan Empty Bunch Stalk (EBS) - Istianto Budhi Rahardja; Yudi Dermawan; Muhammad Soleman (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
Process of sterilizing fresh fruit bunches (FFB) in SOGM Palm Oil Mill (POM) uses automation method, where the opening and closing of the inlet steam valve, exhaust valve and condensate valve based on predetermined time. There are three types of sterilizing program used, ie 84 minutes, 87 minutes and 91 minutes. In order for the sterilizing process to obtain time efficiency and also get the best result, then you should choose one of the best of the three. The purpose of this research is to know the effect of sterilizing time program on Unstripped Bunch (USB), Fruit Loss in Empty Bunch (FEB) and Empty Bunch Stalk (EBS). The method used in this research is to experiment directly to know its influence. The result showed that the length of sterlizing time has a negative effect on USB and FEB, which means the longer the sterilizing time will be the smaller percentage of USB and FEB; and positive effect on EBS, which means the longer the sterilizing time will be the higher the percentage of EBS.